2016
DOI: 10.1159/000444043
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial Adenocarcinoma in SurePath™ Cervical Samples: Cytological Features Revisited

Abstract: Objective: The cytomorphological criteria of malignant endometrial lesions in cervical samples are less well described than those of cervical lesions. We wished to investigate if there were features in SurePath™ liquid-based cytology samples that would facilitate more accurate differentiation between benign and malignant endometrial cells. Study Design: This was a two-phase study, with a review of all SurePath™ samples reported as endometrial adenocarcinoma (n = 42) evaluating 12 cytological features in the fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…Type 2 EmCa show a higher positivity on cervical cytology in accordance with Serdy et al 13 These carcinomas are usually associated with high cellularity, 3‐D clusters or papillae show nuclear pleomorphism, irregularly distributed chromatin and macronucleoli 10‐13 . Hence, these carcinomas are easier to detect on cervical cytology.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Type 2 EmCa show a higher positivity on cervical cytology in accordance with Serdy et al 13 These carcinomas are usually associated with high cellularity, 3‐D clusters or papillae show nuclear pleomorphism, irregularly distributed chromatin and macronucleoli 10‐13 . Hence, these carcinomas are easier to detect on cervical cytology.…”
Section: Discussionsupporting
confidence: 59%
“…A high sensitivity (72.7%) and specificity (100%) in detecting EmCa was obtained by Zhou et al 9 on using ThinPrep Test. A few studies have been conducted, noting importance of endometrial cells on SurePath samples 10‐12 showing variable sensitivity and specificity and positive predictive value (PPV) far lower than those for cervical lesions.…”
Section: Discussionmentioning
confidence: 99%
“…22,23 In a case series described by Gupta et al, the authors have attributed the presence of background keratinized squamoid cells, in two cases of endometrioid carcinoma, to squamoid differentiation. 24 From the current cohort of cervical cytology in patients with histologically proven endometrioid endometrial carcinomas, seven cytology specimens with keratinization in AGC clusters were found. The keratinous material appears as orangeophilic, rigid and acellular fragments within clusters of AGCs or is associated with the AGCs among extracellular material (Figure 1D).…”
Section: Discussionmentioning
confidence: 98%
“…Over 70% of endometrial carcinomas are of endometrioid histology, 20,21 of which many show evidence of squamous differentiation with the formation of squamous morules and even frank squamous differentiation or keratinization 22,23 . In a case series described by Gupta et al., the authors have attributed the presence of background keratinized squamoid cells, in two cases of endometrioid carcinoma, to squamoid differentiation 24 . From the current cohort of cervical cytology in patients with histologically proven endometrioid endometrial carcinomas, seven cytology specimens with keratinization in AGC clusters were found.…”
Section: Discussionmentioning
confidence: 99%